DNA-Protein Interactions Principles and Protocols - Leblanc, Benoît P.; Leblanc, Benoît P.; Rodrigue, Sébastien.; Rodrigue, Sébastien. (Methods in Molecular Biology, 2015)
This fourth edition reflects the most recent technical advances in DNA-protein interaction research. With fully updated chapters that describe techniques proven by their continuous value, the volume also many new chapters have been added that mostly deal with larger-scale experiments, reflecting recent advances in "big biology", combining to offer a very useful compendium of protocols allowing readers to delve into the intricacies of protein-DNA interaction at levels ranging from the very small (as in the case of single-molecule FRET) to the very complex (as with circular chromatin conformation capture, or 4C). Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, DNA-Protein Interactions: Principles and Protocols, Fourth Edition will aid researchers in continuing the incredible progress made in this vital area of study.